What make consumer sign up to PHEVs? Predicting Malaysian consumer behavior in adoption of PHEVs - Adnan, N. (Elsevier Ltd, 2018)
Malaysia is amongst the major energy intense countries and is under an excessive burden to advance its energy efficiency and to also work towards the reduction of its carbon emission. Plug-in Hybrid Electric Vehicles (PHEVs) have the potential to lessen the carbon emission and gasoline consumption in order to alleviate environmental problems. Consequently, attempts are being initiated to popularise the use of PHEVs as the main mode of transportation. The diffusion of PHEV adoption is a positive initiative. A sample of 403 respondents has been collected from Malaysia in order to forecast the customer's intention to adopt PHEVs by using the extended theory of planned behaviour. The empirical outcome using the PLS investigation exposed that all four constructs, subjective norm, personal moral norm, perceived behavioural control, and attitude ominously shows an indirect effect which has inclined towards the Malaysian consumersâ intention to adopt PHEVs. All these four major constructs were significantly predetermined by their respective environmental concern. Whereas, hyperbolic discounting moderated the relationship between intention and adoption. The fostering result verifies that the relevance of the extended TPB had a good explanatory power in the line of predicting the Malaysian consumersâ intention to adopt PHEVs. For future study, grounded by the observed outcome, authors explain the implication aimed at promoting the PHEV adoption. Â© 2018